MANAJEMEN KOMUNIKASI KRISIS PUBLIC RELATIONS PT KAI PASCA-INSIDEN KA ARGO BROMO ANGGREK - Jisca Putri Sagara Hati; Rizki Surya Tawaqal (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2025)
This study stems from the case of the Argo Bromo Anggrek train derailment, which creates significant pressure on the reputation of PT Kereta Api Indonesia and requires a structured and rapid communication response. The purpose of this study is to analyze the application of crisis communication management based on Situational Crisis Communication Theory in an effort to restore public trust. The research used qualitative methods with case studies through in-depth interviews, analysis of official documents, and review of digital content related to the company's response. The results showed that PT KAI implemented a rebuild strategy through public apologies, compensation, and corrective actions combined with a bolstering strategy through the visual presentation of recovery progress in the field. The roles of the Supporting Public External Unit and the Social Media & Corporate Portal Unit complement each other, with the USPE maintaining the consistency of factual information in the mainstream media, while the USPC manages the dynamics of public emotions through more relatable and empathetic content. The findings also show that the company leadership's apology and transparency of information successfully reduced tensions and significantly improved public perception. This study concludes that PT KAI's success was influenced by the integration of consistent messaging, the use of digital sentiment monitoring, and the ability to balance technical explanations and empathy in crisis situations.